Early Marriage and Poverty Levels in Indonesia: A Panel Data Analysis - Purmini, Purmini; Gustina Adela Putri; Lela Rospida (Tinta Emas Institute, 2025)
This study analyzes the influence of early marriage rates on poverty levels in Indonesia. Using secondary data from the Central Statistics Agency (BPS), panel data regression is applied to thirty-four provinces with relatively high poverty and early marriage rates over the 2015–2023 period. The model employs a fixed effect specification and includes economic growth, education level, and unemployment rate as additional explanatory variables. The results show that, simultaneously, economic growth, education level, unemployment rate, and early marriage rate have a significant effect on poverty levels. Partially, economic growth has a positive and significant effect on poverty, indicating that higher economic growth has not yet been accompanied by a reduction in poverty, so that growth is not yet inclusive. Education level has a negative and significant effect on poverty, underscoring the strategic role of education in reducing poverty through improving the quality of human resources. The unemployment rate has a positive and significant effect, meaning that higher unemployment increases the likelihood of poverty. The early marriage rate also has a positive and significant effect, indicating a tendency for early marriage to raise the risk of poverty. The coefficient of determination of 0.98 shows that the variables in the model explain 98 percent of the variation in poverty levels, indicating excellent explanatory power. Overall, the findings confirm that education and unemployment exert a stronger influence on poverty than early marriage, while economic growth has not yet had an inclusive impact on poverty reduction.